Serum proteomic analyses of patients with bone tumours using gel-, Lectin-and mass spectrometry-based strategies / Wan Izlina Wan Ibrahim - Wan Izlina, Wan Ibrahim (2017)
Bone tumour refers to a neoplastic growth which originates from various types of skeletal tissues such as bone, surrounding soft tissues, muscles and ligaments. Bone tumours can be divided into two major groups, benign bone tumour and malignant bone tumour. Due to difficulty and invasive nature of the diagnosis, it is imperative to find new methods or technologies that could be used for early detection of these tumours in order to determine the best course of action for the patient. Currently, there are no known tumour marker (which has been approved by the U.S. Food and Drug Administration) for bone tumours, unlike breast cancer, ovarian cancer and prostate cancer. This study was directed to investigate if there were differences in proteome profiles of patients with various types of bone tumours compared to normal healthy individuals. It also aimed to identify proteins that were aberrantly expressed which may have potential to serve as biomarkers that could differentiate and detect various types of bone tumours. Analysis of silver stained 2DE protein expression profiles using image analysis software demonstrated different altered levels of several high abundance proteins in patients with osteosarcoma (OS), Ewing sarcoma (ES), chondrosarcoma (CS), pleomorphic sarcoma (PS) and giant cell tumour (GCT), relative to age-matched non-tumour healthy individuals. From the 2DE analysis, level serum amyloid A (SAA) demonstrated the highest altered abundance and was found to be significantly increased in patients with OS and PS. Apart from the silver stained 2DE analysis, pooled serum samples from patients with these tumours and healthy controls were also subjected to 2DE Western blotting analysis using enzyme-conjugated champedak galactose binding (CGB)- and champedak mannose binding (CMB)-lectins. Application of CGB- and CMB-lectins as probes enables the detection of O-glycosylated and N-glycosylated proteins, respectively. Three groups of common sarcoma, OS, CS and PS, were selected for further analysis to validate the increased level of SAA. Although the elevation of iv SAA was not statistically significant in patients with CS, unlike OS and PS, it is a malignant tumour with a low metastatic rate and not very aggressive. A comparison can therefore be made between different types of sarcoma correlating to their aggressiveness. A similar trend of altered abundances was also observed when the levels of SAA in the subjects were determined using Western blot, enzyme-linked immunosorbent assay (ELISA) and SWATH™-MS (only in OS). Absolute quantification using multiple reaction monitoring (MRM) further demonstrated that the increased abundance of SAA in patients with OS, CS and PS was mainly attributed to isoform serum amyloid A1 (SAA1). In view of the different degrees of tumour malignancy in OS, CS and PS, this data suggests their apparent correlation with the levels of SAA in the patients and this offers potential to be used as biomarkers to aid early diagnosis of bone tumours, as well as in determining the risk of the malignant tumour.